The economic crisis and medical care usage - Lusardi, A; Schneider, D; Tufano, P (2010)
We use a unique, nationally representative cross-national dataset to document the reduction in individuals' usage of routine non-emergency medical care in the midst of the economic crisis. A substantially larger fraction of Americans have reduced medical care than have individuals in Great Britain, Canada, France, and Germany, all countries with universal health care systems. At the national level, reductions in medical care are related to the degree to which individuals must pay for it, and within countries are strongly associated with exogenous shocks to wealth and employment.